2019
DOI: 10.1096/fj.201801479r
|View full text |Cite
|
Sign up to set email alerts
|

The chronic administration of two novel long‐acting Xenopus glucagon‐like peptide‐1 analogs xGLP159 and XGLP296 potently improved systemic metabolism and glycemic control in rodent models

Abstract: We here reported 2 novel Xenopus glucagon‐like peptide‐1 (xGLP‐1) analogs, xGLP159 and xGLP296, whose therapeutic effects on metabolic efficacy and glycemie control were evaluated in rodents. The in vitro potency of xGLP159 and xGLP296 were investigated on human embryonic kidney 293 cells. The acute glucose‐lowering and insulinotropic effects of xGLP159 and xGLP296 were assessed in the Institute of Cancer Research, Kunming, and diabetic (db/db) mice. The pharmacokinetic profiles of xGLP159 and xGLP296 were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Using previously described methods, activation of human GLP-1R was determined by cAMP formation, and activation of human CCK-1R and CCK-2R was determined by pERK induction. , For each assay, HEK293 cells expressing receptors were grown in DMEM (Dulbecco’s modified Eagle’s medium) supplemented with 10% v/v FBS, 100 units·mL –1 penicillin, 100 μg·mL –1 streptomycin, 2 mM l -glutamine, and 100 μg·mL –1 G418. HEK293 cells expressing GLP-1R were washed, resuspended in assay buffer (20 mM HEPES, 1× HBSS, 2 mM IBMX, 0.1% BSA), and plated into 96-well plates coated with 0.01% poly- l -lysine before testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using previously described methods, activation of human GLP-1R was determined by cAMP formation, and activation of human CCK-1R and CCK-2R was determined by pERK induction. , For each assay, HEK293 cells expressing receptors were grown in DMEM (Dulbecco’s modified Eagle’s medium) supplemented with 10% v/v FBS, 100 units·mL –1 penicillin, 100 μg·mL –1 streptomycin, 2 mM l -glutamine, and 100 μg·mL –1 G418. HEK293 cells expressing GLP-1R were washed, resuspended in assay buffer (20 mM HEPES, 1× HBSS, 2 mM IBMX, 0.1% BSA), and plated into 96-well plates coated with 0.01% poly- l -lysine before testing.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous research identified Xenopus GLP-1, a GLP-1 analogue from amphibians, as an alternative GLP-1R agonist . In addition, some Xenopus GLP-1 derivatives were found to be long-acting GLP-1R agonists with better effects on glycemic control and body weight reduction than those of liraglutide and lixisenatide (a C-terminal modified exendin-4 analogue). , …”
Section: Introductionmentioning
confidence: 99%
“…IPGTT were carried out in normal male Kunming mice (n ¼ 6) using a previously described method with small modication. 35 Mice were fasted overnight (12 h) prior to a 2 g kg À1 i.p. injected of glucose.…”
Section: Intraperitoneal Glucose Tolerance Test (Ipgtt) In Normal Kunmentioning
confidence: 99%
“…Moreover, our previous studies conducted on xGLP-1 revealed that long-acting xGLP-1 derivatives have many beneficial antidiabetic effects, including slowing of gastric emptying, weight loss due to reduced food intake, glucose-dependent promotion of insulin secretion, and increase in β-cell mass/area and pancreas function. 15,16 Many of the dual GLP-1R/GCGR agonists described previously are based on the structures of OXM, glucagon, or exendin-4, leading to a big challenge to tune and optimize the physicochemical properties. 17 Due to its favorable physicochemical properties, xGLP-1 was an attractive scaffold for the development of novel dual GLP-1R and GCGR agonists.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We previously identified a novel GLP-1 analogue (xGLP-1, Figure ) based on Xenopus GLP-1, through rational peptide design and structure–activity relationship (SAR) studies. Moreover, our previous studies conducted on xGLP-1 revealed that long-acting xGLP-1 derivatives have many beneficial antidiabetic effects, including slowing of gastric emptying, weight loss due to reduced food intake, glucose-dependent promotion of insulin secretion, and increase in β-cell mass/area and pancreas function. , …”
Section: Introductionmentioning
confidence: 99%